New Shades of Protectionism and the Role of Multinationals - Joseph Francois; Roman Stöllinger (FIW - Research Centre International Economics, 2009)
Like all crises in the past, the economic downturn of 2008-2009 caused some frictions in the international trading system. Import tariffs, the traditional instrument for protecting domestic industries, however, have not played the primary role in this, particularly not in industrialised countries. The WTO rules have proved to be an efficient shield against a wholesale descent into protectionism in this respect. However, in other policy areas, such as state aid and WTO contingency measures the results are more mixed. While an all-out subsidy war has not broken out, heavy intervention has taken place in the automotive industry. This was much to the benefit of leading multinationals, who have used their international presence and mobility to extract various kinds of public support from governments. Neither governments nor WTO rules have managed to avoid costly subsidies. Indeed governments have found themselves caught in an international subsidy competition inflicted on them by global car manufacturers. This has allowed the car industry to take itself out of the existing international disciplines on subsides. While this is not classical protectionism offered to strictly national industries, we may see a new mutation emerging, wherein multinationals more effectively play governments against each other to lobby for local assistance for what are actually global operations.
Keywords: F13; F23; F42; 330; Protectionism; multinational firms; trade policy coordination